Oviposisi dan Perkembangan Nyamuk Armigeres Pada Berbagai Bahan Kontainer - Endang Puji Astuti; Rina Marina (Loka Litbang Kesehatan Pangandaran, 2009)
Abstract. Armigeres mosquito being the vector responsible for Japanese Encephalitis Virus and Filaria. Variouseffort have been done to control the mosquitoes. Acurated entomological data is needed to support controlmosquito vector, like data hits habitats armigeres. This study is aimed to compare oviposition of armigeres andthe development in various container. the clay container (44 egg)s more many found egg is compared withplastical stuff (11 egg)s. Moulting process of armigeres almost the same to culicinae, that is average ± 2 - 3days. Mosquito development in this laboratory test only until third generation (f3). Rearing of armigeres neededthe enviromental kondusif with nature habitat.